Enfermedades parasitarias transmitidas por las garrapatas en caninos domésticos - Vargas Cabrera, Yomira Anais (2021)
The presence of parasitic diseases in canines is very frequent, even more so in abandoned or stray animals, due to the difficulty of controlling them, it is important to know and identify parasitic diseases since each one has different symptoms and that they affect to the canine population of a sector or community. Ticks are hematophagous ectoparasites of amphibians, reptiles, birds and mammals, transmitting important diseases and the most common in canines such as: babesia, ehrlichiosis, anaplasmosis, Lyme disease, these diseases produce common gastrointestinal, cardiopulmonary, skeletal muscle, neuronal, among the main ones, some of the diseases that are produced by contagion through tick bites are serious, even fatal. From a health perspective, their importance lies in the fact that they can act as vectors of pathogenic microorganisms such as protozoa, rickettsiae, spirochetes and viruses that affect domestic animals and man, in addition to their potential to cause toxicosis, paralysis, irritation and allergy to their hosts. This research will allow the implementation of control strategies for this infection, which additionally represents a risk of contagion for other canines and can also be a risk for public health.